Sectoral R&D intensity and exchange rate volatility: A panel study on economies of the OECD - Prashanth Mahagaonkar; Rainer Schweickert; Aditya S. Chavali (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
A recent literature has pointed at potential negative effects of exchange rate volatility on innovation. In this paper, we propose that there may be a direct effect as well as an indirect effect via export activity. We test these hypotheses for sectoral R&D intensities using OECD panel data for manufacturing and services sectors for 14 OECD economies and the years 1987 - 2003. We find that the direct negative effect of volatility is pronounced in manufacturing sector but is dominated by the indirect effect via the export channel. Services do not face any effects of volatility on R&D intensities. While it is not clear which channel dominates our results confirm that there is a negative volatility affect related to openness on a sectoral level.
Keywords: E32; F31; O32; 330; R&D intensity; Innovation; Real Exchange Rate; Volatility; Exports; OECD-Countries; Wechselkurs; Volatilität; Innovation; Industrielle Forschung; Export; Kaufkraftparität; Schätzung; OECD-Staaten